2019
DOI: 10.1186/s12885-019-5448-0
|View full text |Cite
|
Sign up to set email alerts
|

A leucine-rich diet modulates the mTOR cell signalling pathway in the gastrocnemius muscle under different Walker-256 tumour growth conditions

Abstract: Background The exact signalling mechanism of the mTOR complex remains a subject of constant debate, even with some evidence that amino acids participate in the same pathway as used for insulin signalling during protein synthesis. Therefore, this work conducted further study of the actions of amino acids, especially leucine, in vivo , in an experimental model of cachexia. We analysed the effects of a leucine-rich diet on the signalling pathway of protein synthesis in musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…Previously, we demonstrated that leucine supplementation increased the mTOR signalling, which was reflected in the maintenance of the total muscle protein net [ 51 ] ( Figure 7 ). Moreover, a leucine-rich diet modulated pro- and anti-cachectic cytokines and the key proteins involved in the ubiquitin-proteasome pathway in gastrocnemius muscle tissue [ 14 ].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previously, we demonstrated that leucine supplementation increased the mTOR signalling, which was reflected in the maintenance of the total muscle protein net [ 51 ] ( Figure 7 ). Moreover, a leucine-rich diet modulated pro- and anti-cachectic cytokines and the key proteins involved in the ubiquitin-proteasome pathway in gastrocnemius muscle tissue [ 14 ].…”
Section: Discussionmentioning
confidence: 94%
“…We conducted previous studies, with pair-fed groups, where we supplied the same amount of diet ingested by the groups with tumour to the other non-tumour-bearing groups, that is, the weight of the diet provided was normalised by the weight of the ingestion of the tumour group. Therefore, we have already validated in our laboratory that the amount of food ingested did not interfere with the parameters analysed in our experiments [ 14 , 51 ].…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous studies have shown that the Walker 256 tumour growth-an experimental model of cachexia-led to metabolomic [13] and metabolic [14] alterations, and increased the muscle proteasomal activity [15,16] in adult rats. However, to the best of our knowledge, the biomarkers-related to sarcopenia and cachexia in senile cancer animals are not yet totally known.…”
Section: Introductionmentioning
confidence: 99%